Intelligent detection method for ultra-black composite film
By spraying multi-walled carbon nanotubes and composite ink on ultra-black composite films, a honeycomb structure is formed, and conductivity image reconstruction technology is used to solve the problem of damage monitoring of ultra-black materials in space environments, real-time damage detection and positioning are achieved, and real-time damage detection and positioning are improved. The reliability and self-perception capabilities of the optical system.
Patent Information
- Application Number
- CN202411751796.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-02
AI Technical Summary
In space environments, ultra-black materials are easily damaged by micrometeor impacts, resulting in a decrease in the resolution of the optical system. Traditional non-destructive detection technology cannot achieve real-time monitoring, making it difficult to detect structural aging or damage in a timely manner, affecting the reliability of the optical system.
Using conductivity image reconstruction technology, by spraying multi-wall carbon nanotube color paste and composite ink on ultra-black composite film, a dense layer and honeycomb structure is formed, and a self-adsorption freezer and voltage acquisition circuit are used to perform current excitation and voltage distribution are measured. , reconstruct the conductivity image to realize intelligent self-monitoring and positioning of local damage.
Real-time online monitoring of ultra-black composite films is realized, which can promptly detect damage, reduce maintenance costs, improve the reliability and self-perception of the optical system, and does not affect the optical performance of the film.
Smart Images

Figure CN119224065A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film detection, and in particular relates to an intelligent detection method for an ultra-black composite film. Background Art
[0002] Super black materials (also called super light-absorbing materials) are a new type of material that can efficiently absorb incident light. They have extremely high light absorption rates and have broad application prospects in scientific research and engineering applications. For example, outside the field of view of the optical system, non-imaging light such as sunlight and geothermal light (sunlight scattered by the earth's atmosphere) enters the system and reaches the detector through multiple reflections, refractions, scatterings, and diffractions of the internal components of the system (optical surfaces and mechanical surfaces). In addition, residual reflections, scatterings, and diffractions caused by the roughness, surface defects, and surface contamination of the optical components inside the optical system cause some of the light involved in imaging to reach the system image plane through an abnormal path inside the system, forming non-imaging light with optical noise. By coating the inner wall of the optical system's light shield with super light-absorbing materials, these stray lights can be effectively suppressed, improving the detection accuracy, resolution, and detection capabilities of the optical system for dim targets. However, the number of micrometeorites generated by the impact of various celestial bodies in space is large and widely distributed. Satellites and detectors working in such an environment are often faced with the "attack" of micrometeorites. Due to the large relative speed between them and the spacecraft, they will generate large energy when colliding with the spacecraft, which will inevitably damage the optical system, especially the ultra-black material in the light shield, which will hinder its suppression of stray light and reduce the resolution of the optical system. In addition, due to the complex composition of space optical payloads, when imaging problems occur, the entire system needs to be checked, but the structural state of the ultra-black material inside the light shield cannot be known in time, making the troubleshooting process more difficult. Real-time monitoring of ultra-black materials can timely reflect the structural aging or damage caused by external loads and internal defects, so as to timely discover and warn, which can greatly reduce maintenance time and cost and improve the self-perception ability of the overall reliability of the optical system.
[0003] In order to avoid structural inspection from damaging composite materials and affecting their continued use, researchers at home and abroad have developed a variety of non-destructive testing technologies for monitoring the service status of composite materials, including ultrasonic method, X-ray detection method, electrical sensing and other methods. The ultrasonic method detects damage and defects in materials based on the difference between the reflection attenuation and resonance of ultrasonic waves in composite materials in the damaged defect area and the intact area. However, this method must know the approximate location of the damage in advance and cannot achieve real-time monitoring. The X-ray detection method uses the radiation energy of high-energy electromagnetic waves that is not absorbed after passing through the material to image on the photoelectric sensor for detection. Due to the characteristics of high cost and offline detection, it is difficult to achieve field application. The electrical sensing method forms a sensor network by installing sensors on the surface or inside of the material. When facing external impact, structural strain and internal damage, it monitors according to the local signal changes in the sensor network. It has the advantages of online and local monitoring. However, the traditional electrical sensing method requires a large sensor network, which increases the weight of the structure and the difficulty of installation. It is difficult to achieve a perfect match between the sensor itself and the composite material, which limits its application in material health monitoring. Therefore, it is urgent to develop advanced electrical sensing technology to realize online real-time monitoring of composite material damage, fully understand the health status of the material, and ensure its reliable service in the environment. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an intelligent detection method for an ultra-black composite film. By using conductivity image reconstruction technology to detect the conductivity changes of the ultra-black film, intelligent self-monitoring and positioning of local damage of the ultra-black composite film can be achieved without introducing external sensors.
[0005] The object of the present invention is to provide an intelligent detection method for ultra-black composite film, comprising the following steps: S1, spraying a multi-walled carbon nanotube color paste on the surface of a substrate, and obtaining a dense film after drying; S2, spraying the composite ink on the surface of the dense film to form a composite film; S3, freezing the composite film with liquid nitrogen by a self-adsorption flat plate freezer, and then freeze-drying the composite film by a freeze dryer, and obtaining an ultra-black composite film by plasma surface treatment; S4, electrodes are drawn out around the ultra-black composite film, and the number of electrodes on each side is 4 or 6; S5, connecting the electrodes on the ultra-black composite film to a voltage acquisition circuit, using two adjacent electrodes as input points and output points of the excitation current, measuring the voltage values at the remaining electrodes, and obtaining the voltage distribution at each electrode of the ultra-black composite film before damage; Repeating the steps for the damaged ultra-black composite film to obtain the voltage distribution of the damaged ultra-black composite film; S6. Reconstruct an image based on the voltage distribution before and after the ultra-black composite film is damaged to obtain a distribution imaging diagram of the conductivity of the ultra-black composite film; and realize intelligent self-monitoring and positioning of local damage of the ultra-black composite film based on the distribution imaging diagram.
[0006] In one embodiment of the present invention, in S1, the process parameters of the spraying are: air pressure of 0.3MPa-0.5MPa, flow rate of 20mL / min-30mL / min, spraying distance of 200mm-400mm, and time of 10s-20s; The drying temperature is 80°C-100°C, and the drying time is 20min-30min.
[0007] In one embodiment of the present invention, in S2, the preparation of the composite ink includes the following steps: dissolving the multi-walled carbon nanotube color paste described in S1 in water and stirring evenly, continuing to add a binder, a metal oxide filler, a thickener, a defoaming agent and an auxiliary agent and stirring evenly to obtain a composite ink; the multi-walled carbon nanotube color paste is obtained by mixing multi-walled carbon nanotubes, a surface modifier, water and an alcohol solvent.
[0008] In one embodiment of the present invention, the weight parts of the components in the composite ink are: 70-90 parts of multi-walled carbon nanotube color paste, 5-15 parts of water, 1-5 parts of binder, 1-5 parts of metal oxide filler, 0.5-1 parts of thickener, 0.5-1 parts of defoamer, and 1-5 parts of additive; The mass ratio of the multi-walled carbon nanotubes, the surface modifier, water and the alcohol solvent in the multi-walled carbon nanotube color paste is (5-10): (4-10): (70-90): (5-12).
[0009] In one embodiment of the present invention, the binder is selected from one or more of acrylic resin, silicone-modified acrylic resin and epoxy resin; The metal oxide filler is selected from nano zinc oxide and / or nano titanium dioxide; The thickener is selected from hydroxyethyl cellulose and / or associative polyurethane thickener; The defoamer is selected from polysiloxane defoamer and / or BASF Mart defoamer; The auxiliary agent is selected from isopropanol and / or ethylene glycol; The surface modifier is selected from one or more of disodium distyryl diphenyl disulfonate, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate; The alcohol solvent is selected from one or more of ethanol, isopropanol and ethylene glycol.
[0010] In one embodiment of the present invention, in S2, the process parameters of the spraying are: air pressure of 0.3MPa-0.5MPa, flow rate of 20mL / min-30mL / min, spraying distance of 200mm-400mm, and time of 40s-80s.
[0011] In one embodiment of the present invention, in S3, the self-adsorption plate freezer comprises: The first cavity has a micropore array on its surface; the first cavity is connected to an exhaust pipe; the exhaust pipe is connected to a vacuum pump; The second cavity is located below the first cavity; the second cavity is provided with an infusion port and an exhaust port; the infusion port is used for infusing liquid nitrogen; the exhaust port is used for exhausting the air in the second cavity.
[0012] In one embodiment of the present invention, in S3, the temperature of the liquid nitrogen freezing is -150°C to -100°C, and the time is 1 min to 2 min; The freeze drying process has a vacuum degree of 2Pa-10Pa, a temperature of -20°C to -40°C, and a time of 5h-10h; The plasma surface treatment has a vacuum degree of 20Pa-40Pa, a power of 100W-150W, and a time of 1min-5min.
[0013] In one embodiment of the present invention, in S5, the measurement of the voltage distribution of the ultra-black composite film specifically includes the following steps: connecting the electrodes on the ultra-black composite film to the voltage acquisition circuit, using two adjacent electrodes as the input point and output point of the excitation current, and measuring the voltage value between each remaining electrode and the current output point at the same time, and performing current excitation between each remaining adjacent electrode pair in turn until all electrode pairs are tested, thereby obtaining the voltage distribution at each electrode of the ultra-black composite film before damage.
[0014] In one embodiment of the present invention, in S6, the software used for the image reconstruction is MATLAB software.
[0015] The technical solution of the present invention has the following advantages over the prior art: The ultra-black composite film of the present invention has a multi-layered and multi-level composite light-trapping structure, including: a vertically ordered array of micrometer-scale honeycomb holes, and a continuous network of uneven carbon nanotubes constituting the honeycomb wall. The micro-nano honeycomb structure can reflect and absorb incident light multiple times, and the uneven carbon nanotube honeycomb wall can scatter the incident light multiple times, so that the reflected light is greatly reduced, thereby obtaining super light absorption ability.
[0016] The ultra-black composite film of the present invention has good electrical conductivity, making it a sensitive medium. When damaged, its conductivity changes greatly, and the local damage intelligent self-monitoring and positioning of the ultra-black composite film can be realized through the conductivity image reconstruction technology. Online monitoring is realized without introducing external sensors, and the optical properties of the ultra-black composite film itself are not affected.
[0017] The method described in the present invention uses a two-time spray-drying technology. After the composite ink is sprayed on the substrate for the first time, a heating and drying treatment is performed to form a dense carbon nanotube film on the film surface, which makes the ultra-black composite film have good conductivity. The second spraying of the composite ink is carried out for liquid nitrogen freezing and freeze drying to form a layer with a honeycomb-like micro-nano light trapping structure on the original dense carbon nanotube layer, which on the one hand improves the optical properties of the film and makes it an ultra-black composite film; on the other hand, although the overall conductivity is reduced, the dense carbon nanotube film is formed by the first spraying, so that the overall conductivity of the ultra-black composite film is still at a good level. When the ultra-black composite film is subjected to current excitation and the voltage value is collected, the ultra-black composite film with better conductivity has a larger change in conductivity after being damaged, and the position displayed by the reconstruction of the conductivity image is also clearer and more accurate, thereby realizing the function of the ultra-black composite film for self-sensing monitoring of structural health.
[0018] The method described in the present invention combines spraying technology, freezing technology and conductivity image reconstruction technology, and has the advantages of simple process flow, suitability for large-area preparation, and precise positioning. Compared with traditional offline detection, it is also faster and more convenient, and can significantly improve the early warning capability of ultra-black composite film when serving in complex conditions such as space environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 is a schematic diagram of a self-adsorption plate freezer of the present invention; Figure 2 Schematic diagram of the device for intelligent detection of the ultra-black composite film and the imaging results of Example 1 of the present invention; wherein (a) is a diagram of the intelligent detection device, (b) is a schematic diagram of the ultra-black composite film with through-hole damage, and (c) is the positioning imaging of the ultra-black composite film with through-hole damage; Figure 3 The imaging results of the film of Comparative Example 1 of the present invention are shown in FIG. 1 ; wherein (a) is a schematic diagram of an ultra-black composite film having through-hole damage, and (b) is a positioning imaging of an ultra-black composite film having through-hole damage; Figure 4The macroscopic optical photographs of the ultra-black composite film of the present invention are shown in FIG. 1 , wherein (a) is a macroscopic optical photograph of the ultra-black composite film before the electrode is fixed, and (b) is a macroscopic optical photograph of the ultra-black composite film after the circuit is connected; Figure 5 The microscopic morphology SEM images of the ultra-black composite film of the present invention; wherein (a) is micrometer scale; (b) is nanometer scale; Figure 6 is the integrating sphere diffuse reflectance of the ultra-black composite film of the present invention. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0021] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0022] In the present invention, unless otherwise specified, the multi-walled carbon nanotubes used in the embodiments of the present invention are purchased from Qihang Technology, with a length of about 10μm-100μm and a diameter of about 10nm-20nm; the binder acrylic resin is purchased from Shanghai Tuyue New Materials Technology Co., Ltd., model PQ673; the associative polyurethane thickener is purchased from Guangzhou Huitu New Materials Co., Ltd., model HT-105; the polysiloxane defoamer is purchased from Guangzhou Tuosheng New Materials Co., Ltd., model BYK-025; the electrode is an iron-plated copper electrode clip.
[0023] In the present invention, unless otherwise specified, the self-adsorption plate freezer ( Figure 1 ) comprises: a first cavity 1, on the surface of which a micropore array 1.1 is provided; and the side wall of the first cavity 1 is connected to an exhaust pipe 2; the exhaust pipe 2 can be connected to a vacuum pump; a second cavity 3, located below the first cavity 1, is used to charge and discharge low-temperature liquid nitrogen, so that the self-adsorption freezing processor can obtain a low temperature, and the low temperature created by the liquid nitrogen is used to quickly freeze the wet composite film; the front side wall of the second cavity 3 is provided with an infusion port 4 (funnel shape) for infusing liquid nitrogen; the front side wall of the second cavity 3 is provided with an exhaust port 5 for exhausting the air in the second cavity 3. Example 1
[0024] Reference Figure 2 As shown, the intelligent detection method of the ultra-black composite film of the present invention specifically comprises the following steps: S1: Preparation of composite ink S11. Preparation of multi-walled carbon nanotube color paste: weigh 6 parts of multi-walled carbon nanotubes, 4 parts of surface modifier sodium dodecylbenzene sulfonate, 80 parts of water, and 10 parts of alcohol solvent isopropanol, add them into a dispersion tank, first use a mechanical shear disperser to stir and disperse at a stirring speed of 1000 rpm for 30 minutes, then use a power of 500 W to ultrasonically disperse for 30 minutes, and then use a high-pressure homogenizer to disperse 5 times at a pressure of 800 bar to obtain a multi-walled carbon nanotube color paste.
[0025] S12. Preparation of composite ink: Take 85 parts of multi-walled carbon nanotube color paste and add it to a dispersion tank filled with 12 parts of deionized water, and stir and mix it for 60 minutes using a mechanical shear disperser at a stirring speed of 2000rpm; continue to slowly add 5 parts of a binder acrylic resin emulsion with a solid content of 40%, 1 part of a metal oxide filler nano titanium dioxide, 0.5 parts of an associative polyurethane thickener, 0.5 parts of a polysiloxane defoamer and 1 part of an auxiliary isopropanol under stirring conditions, and continue to stir and mix for 60 minutes to obtain a composite ink.
[0026] S2: Preparation of composite films S21, treating the surface of the flexible polyimide film substrate with a low-temperature surface plasma having a power of 1 kW for 20 seconds, and then pickling with 10% by volume sulfuric acid for 10 minutes to complete the hydrophilic treatment of the surface of the flexible polyimide film substrate to obtain a pretreated substrate; S22, by spraying technology, set the air pressure to 0.3MPa, the flow rate to 30mL / min, the spraying distance to 250mm, the time to 10s, spray the multi-walled carbon nanotube color paste on the surface of the pretreated substrate, put it in an oven at 80°C for 30min to obtain a dense film; S23, using spraying technology, setting the air pressure to 0.3 MPa, the flow rate to 30 mL / min, the spraying distance to 250 mm, and the time to 80 s, spraying the composite ink on the surface of the dense film to form a composite film; S3: Preparation of ultra-black composite films S31, spreading the composite film on the surface of a self-adsorption plate freezer filled with liquid nitrogen and freezing it at -120°C for 1 minute; S32, then freeze-drying in a freeze dryer at a vacuum degree of 5 Pa and a temperature of -40°C for 8 hours, forming a vertically arranged micro-nano honeycomb structure by liquid nitrogen freezing and freeze drying; S33, finally, the surface was treated with oxygen plasma for 5 min under the conditions of a vacuum degree of 40 Pa and a power of 120 W in the chamber, and the honeycomb wall at the top of the vertically and orderly arranged micro-nano honeycomb structure was etched to obtain an ultra-black composite film; S4, cut the ultra-black composite film into a 10 cm × 10 cm square, and evenly clamp the electrode clips connected with wires around the film (4 electrodes on each side); S5, connecting the electrodes on the ultra-black composite film to the voltage acquisition circuit, using two adjacent electrodes as the input point and output point of the excitation current (DC current is 100mA), and measuring the voltage value between each remaining electrode and the current output point at the same time, and performing current excitation between each remaining adjacent electrode pair in turn until all electrode pairs are tested, and obtaining the voltage distribution at each electrode of the ultra-black composite film before damage; Refer to Figure 2 Damaging the ultra-black composite film, repeating the steps for the damaged ultra-black composite film, and obtaining a voltage distribution of the damaged ultra-black composite film; S6. Using the open source EIDORS program in MATLAB software, according to the parameters such as the size of the ultra-black composite film in the experiment, the distribution position of the electrodes, the number of electrodes, etc., a calculation model identical to the experimental ultra-black composite film is established, the voltage distribution of the ultra-black composite film before and after damage is imported, and image reconstruction is performed to obtain the distribution imaging map of the conductivity of the ultra-black composite film. The structural state of the ultra-black composite film can be reflected according to the conductivity distribution, thereby realizing the intelligent self-monitoring and positioning of the damage of the ultra-black composite film. By measuring the voltage distribution before and after damage and importing the model, the conductivity distribution map of the film surface before and after damage is obtained. In the damaged area, the structure is destroyed and the conductive path is interrupted, causing the conductivity to decrease. The change area on the conductivity distribution map corresponds to the area where the conductivity decreases. By observing the changes in the conductivity distribution map, the damage position on the film surface can be quickly detected.
[0027] Figure 2 The schematic diagram and imaging results of the intelligent self-detection and positioning device for local damage of ultra-black composite film. Figure 2 (a) is a schematic diagram of the damage detection and positioning device and circuit connection (taking the 16-electrode conductivity image reconstruction device as an example). Each ultra-black composite film is evenly distributed with 4 electrodes, and the electrodes are connected to a device for providing excitation current and voltage detection through wires. The voltage measuring device can transmit the measured voltage value to the computer. When the ultra-black composite film is hit by an external object and holes appear, its surface structure is destroyed. Under the same current excitation, the voltage value measured at each electrode changes. The voltage values before and after the damage are transmitted to the computer. According to the open source EIDORS program in MATLAB, a model identical to the test sample and the connected electrodes is established. The voltage distribution before and after the damage is input to obtain the change diagram of the overall conductivity of the ultra-black composite film. Figure 2 (b) is a schematic diagram of the ultra-black composite film after being connected to the test device, and penetrating hole damage is created on the film. Figure 2 (c) is the conductivity change image of the ultra-black composite film obtained by collecting voltage values and reconstructing the conductivity image. The conductivity change area basically coincides with the actual location of damage, indicating that this method can monitor and locate the damage on the ultra-black film well. Comparative Example 1
[0028] Basically the same as Example 1, except that no dense film is prepared.
[0029] The imaging results of the composite film are shown in Figure 3 As shown. Figure 3 It can be seen that for the film that is directly sprayed with composite ink and freeze-dried without spraying carbon nanotube color paste, the overall conductivity is poor due to the lack of a dense carbon nanotube layer. Under the same current excitation, the measured voltage signal is weak and the error is large. When the MATLAB model is imported to reconstruct the image, the positioning and detection capabilities have large errors due to the large error in the damage position on the film. Test Example 1
[0030] Figure 4 (a) is a macroscopic optical photograph of the ultra-black composite film before the electrode is fixed. The ultra-black composite film is dark black as a whole, with uniform color and no visible reflection to the naked eye. Figure 4 (b) is a macroscopic optical photograph of the ultra-black composite film after connecting to the circuit. Since the fixed electrodes only occupy a small area around the ultra-black composite film, they will not affect the overall optical properties of the ultra-black composite film. Test Example 2
[0031] The microstructure of the ultra-black composite film was characterized by SEM. Figure 5 As shown. Figure 5 (a) It can be seen that the ultra-black composite film prepared by this method presents a bionic honeycomb porous structure on a micrometer scale, and the diameter of the honeycomb holes is distributed in an area of about 10μm-50μm. This vertical hole structure allows light to be absorbed and reflected multiple times inside it, which can effectively "capture" light. Figure 5 (b) It can be seen that at the nanoscale, the carbon nanotubes in the honeycomb skeleton are intertwined with each other to form a continuous and loose carbon nanotube network. On the one hand, the nanopores can further scatter light, and on the other hand, the carbon nanotubes contact each other to form a good electron transmission channel, becoming a well-conductive whole. Test Example 3
[0032] The LAMBDA 1050+ UV-visible-near-infrared spectrophotometer with an integrating sphere accessory was used to test the integrating sphere diffuse reflectance curve of the ultra-black composite film. The band range is 400nm-2000nm. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the average reflectivity of the ultra-black composite film in the visible and near-infrared (Vis / NIR) bands is ~0.4% (absorption ~99.6%).
[0033] In summary, the vertically arranged bionic micro-nano honeycomb structure of the ultra-black composite film can reflect, absorb and scatter the incident light multiple times, and obtain super light absorption ability; in addition, the multi-walled carbon nanotubes form a honeycomb structure under the extrusion of ice crystals. As the main body of the honeycomb skeleton, the multi-walled carbon nanotubes with a large aspect ratio are intertwined with each other, becoming a good electron transmission channel, forming an integral and continuous conductive network. When damage occurs on the ultra-black composite film, the structure of the damaged area is destroyed, resulting in the interruption of the conductive network in the area, and the conductivity changes. By measuring the voltage value at each electrode position, the conductivity image reconstruction method can be used to image the overall conductivity distribution of the ultra-black composite film, and the change in conductivity before and after damage can be used to reflect the structural change. In this way, the in-situ and online self-sensing structural health monitoring of the ultra-black composite film can be realized without affecting the normal use of the ultra-black composite film, and the real-time structural perception, damage monitoring and positioning of the ultra-black composite film can be realized.
[0034] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. An intelligent detection method for ultra-black composite film, characterized in that: The following steps are involved: S1, spraying a multi-walled carbon nanotube color paste on the surface of a substrate, and obtaining a dense film after drying; S2, spraying the composite ink on the surface of the dense film to form a composite film; S3, freezing the composite film with liquid nitrogen by a self-adsorption flat plate freezer, and then freeze-drying the composite film by a freeze dryer, and obtaining an ultra-black composite film by plasma surface treatment; S4, electrodes are drawn out around the ultra-black composite film, and the number of electrodes on each side is 4 or 6; S5, connecting the electrodes on the ultra-black composite film to a voltage acquisition circuit, using two adjacent electrodes as input points and output points of the excitation current, measuring the voltage values at the remaining electrodes, and obtaining the voltage distribution at each electrode of the ultra-black composite film before damage; Repeating the steps for the damaged ultra-black composite film to obtain the voltage distribution of the damaged ultra-black composite film; S6. Reconstruct an image based on the voltage distribution before and after the ultra-black composite film is damaged to obtain a distribution imaging diagram of the conductivity of the ultra-black composite film; and realize intelligent self-monitoring and positioning of local damage of the ultra-black composite film based on the distribution imaging diagram.
2. The intelligent detection method of ultra-black composite film according to claim 1, characterized in that: In S1, the process parameters of the spraying are: air pressure of 0.3MPa-0.5MPa, flow rate of 20mL / min-30mL / min, spraying distance of 200mm-400mm, and time of 10s-20s; The drying temperature is 80°C-100°C, and the drying time is 20min-30min.
3. The intelligent detection method of ultra-black composite film according to claim 1, characterized in that: In S2, the preparation of the composite ink includes the following steps: dissolving the multi-walled carbon nanotube color paste described in S1 in water and stirring evenly, and continuing to add a binder, a metal oxide filler, a thickener, a defoaming agent and an auxiliary agent and stirring evenly to obtain a composite ink; the multi-walled carbon nanotube color paste is obtained by mixing multi-walled carbon nanotubes, a surface modifier, water and an alcohol solvent.
4. The intelligent detection method of ultra-black composite film according to claim 3 is characterized in that: The weight parts of the components in the composite ink are: 70-90 parts of multi-walled carbon nanotube color paste, 5-15 parts of water, 1-5 parts of binder, 1-5 parts of metal oxide filler, 0.5-1 parts of thickener, 0.5-1 parts of defoamer, and 1-5 parts of additives; The mass ratio of the multi-walled carbon nanotubes, the surface modifier, water and the alcohol solvent in the multi-walled carbon nanotube color paste is (5-10): (4-10): (70-90): (5-12).
5. The intelligent detection method of ultra-black composite film according to claim 3, characterized in that: The binder is selected from one or more of acrylic resin, silicone-modified acrylic resin and epoxy resin; The metal oxide filler is selected from nano zinc oxide and / or nano titanium dioxide; The thickener is selected from hydroxyethyl cellulose and / or associative polyurethane thickener; The defoamer is selected from polysiloxane defoamer and / or BASF Mart defoamer; The auxiliary agent is selected from isopropanol and / or ethylene glycol; The surface modifier is selected from one or more of disodium distyryl diphenyl disulfonate, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate; The alcohol solvent is selected from one or more of ethanol, isopropanol and ethylene glycol.
6. The intelligent detection method of ultra-black composite film according to claim 1, characterized in that: In S2, the process parameters of the spraying are: air pressure of 0.3MPa-0.5MPa, flow rate of 20mL / min-30mL / min, spraying distance of 200mm-400mm, and time of 40s-80s.
7. The intelligent detection method of ultra-black composite film according to claim 1, characterized in that: In S3, the self-adsorption plate freezer comprises: The first cavity has a micropore array on its surface; the first cavity is connected to an exhaust pipe; the exhaust pipe is connected to a vacuum pump; The second cavity is located below the first cavity; the second cavity is provided with an infusion port and an exhaust port; the infusion port is used for infusing liquid nitrogen; the exhaust port is used for exhausting the air in the second cavity.
8. The intelligent detection method of ultra-black composite film according to claim 1, characterized in that: In S3, the temperature of the liquid nitrogen freezing is -150°C to -100°C, and the time is 1 min to 2 min; The freeze drying process has a vacuum degree of 2Pa-10Pa, a temperature of -20°C to -40°C, and a time of 5h-10h; The plasma surface treatment has a vacuum degree of 20Pa-40Pa, a power of 100W-150W, and a time of 1min-5min.
9. The intelligent detection method of ultra-black composite film according to claim 1, characterized in that: In S5, the measurement of the voltage distribution of the ultra-black composite film specifically includes the following steps: connecting the electrodes on the ultra-black composite film to the voltage acquisition circuit, using two adjacent electrodes as the input point and output point of the excitation current, and measuring the voltage value between each remaining electrode and the current output point at the same time, and performing current excitation between each remaining adjacent electrode pair in turn until all electrode pairs are tested, thereby obtaining the voltage distribution at each electrode of the ultra-black composite film before damage.
10. The intelligent detection method of ultra-black composite film according to claim 1, characterized in that: In S6, the software used for image reconstruction is MATLAB software.
Citation Information
Patent Citations
Novel biological and gas sensor based on bionic honeycomb coal aerogel material
CN104730115A
CNT (carbon nanotube)-polymer laminated composite flexible transparent electrode and preparation method thereof
CN105321592A
Structural damage real-time monitoring and positioning method
CN107655937A
Preparation method of carbon nanotube-doped tungsten disulfide composite film electrode
CN110526296A
High-thermal-conductivity graphene composite film and preparation method thereof
CN116003148A